Cervical puncture to deliver nusinersen in patients with spinal muscular atrophy. (14th August 2018) - Veerapandiyan, Aravindhan; Pal, Ria; D'Ambrosio, Stephen; Young, Iris; Eichinger, Katy; Collins, Erin; Westesson, Per-Lennart; Kwon, Jennifer; Ciafaloni, Emma
Abstract : Objective: To report our experience delivering intrathecal nusinersen through cervical puncture in patients with spinal muscular atrophy (SMA) with no lumbar access. Background: SMA is a neuromuscular disorder characterized by profound muscle weakness, atrophy, and paralysis due to degeneration of the anterior horn cells. Nusinersen, the first Food and Drug Administration–approved treatment for SMA, is administered intrathecally via lumbar puncture; however, many patients with SMA have scoliosis or solid spinal fusion with hardware that makes lumbar access impossible. Studies in primates have demonstrated better spinal cord tissue concentration with intrathecal injections than with intracerebral ventricular injections. Therefore we have used C1/C2 puncture as an alternative to administer nusinersen. Method: Retrospective chart review. Results: Intrathecal nusinersen via cervical puncture was given to 3 patients who had thoracic and lumbosacral spinal fusion: a 12-year-old girl with type 1 SMA and 2 17-year-old girls with type 2 SMA. Cervical puncture was performed without deep sedation under fluoroscopic guidance using a 25-G or a 24-G Whitacre needle in the posterior aspect of C1-C2 interspace and full dose of nusinersen (12 mg/5 mL) was injected after visualizing free CSF flow. Patients completed their 4 loading doses and first maintenance dose of nusinersen, and 15 procedures were successful and well-tolerated. Conclusion: Cervical puncture is a feasible alternative delivery route to administer intrathecal nusinersen in patients with longstanding SMA and spine anatomy precluding lumbar access when done by providers with expertise in this procedure.